1996
DOI: 10.1269/jrr.37.38
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Profiles of Neutron and X-Irradiated Small Intestine.

Abstract: This paper describes the response of mouse small intestine, at several time points after treatment with neutron or X-irradiation, using doses expected to give similar effects in terms of crypt/microcolony survival. Using resin histology, the effects of radiation on the numbers of duodenal cell types and measurements of tissue areas were assessed. The results for individual parameters and for an estimate of overall damage are given in a data display, which summarises the morphological profile of the organ after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Leucocytic infiltration in and around the affected crypts was occasionally shown, indicating that these cells suffered from severe pycnotic changes. These results are highly in agreement with those obtained from other experimental models (Carr et al, 1996). Moreover the lumen of many crypts became conspicuous, accompanied with extreme squamation of the lining epithelium.…”
Section: Resultssupporting
confidence: 92%
“…Leucocytic infiltration in and around the affected crypts was occasionally shown, indicating that these cells suffered from severe pycnotic changes. These results are highly in agreement with those obtained from other experimental models (Carr et al, 1996). Moreover the lumen of many crypts became conspicuous, accompanied with extreme squamation of the lining epithelium.…”
Section: Resultssupporting
confidence: 92%
“…Two genes involved in cell wall function (ECM4 and SPI1) have been associated with toxin resistance and acid stress. It has also been reported that neutron irradiation causes more damage to the cell wall and produces more early effects than X-ray treatment of the intestinal wall of mice [56].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this small 25% reduction of the cell number may concern an important number of secretory cells, leading to a significant loss of secretory response. Indeed, the proportion of cryptal cells of different types has been shown to vary differently after an irradiation (8). The hyporesponsiveness to VIP is transitory, because I sc responses returned to normal values at 7 days after exposure.…”
Section: Discussionmentioning
confidence: 99%